A BULLET FOR INVARIANCE: ANOTHER ARGUMENT AGAINST THE INVARIANCE CRITERION FOR LOGICAL TERMS. - ZINKE, ALEXANDRA (Journal of Philosophy, 2018)
The article focuses on the philosophy of logical terms. It offers information on the significance of isomorphism on the semantic demarcation criterion of logical term. It also presents information on topics including individuation of logical term, metaphysical necessity, and non-formal metalanguageto the formal object language.